2003
DOI: 10.1182/blood-2002-08-2622
|View full text |Cite
|
Sign up to set email alerts
|

Two histone deacetylase inhibitors, trichostatin A and sodium butyrate, suppress differentiation into osteoclasts but not into macrophages

Abstract: Histone deacetylase (HDAC) inhibitors are emerging as a new class of anticancer therapeutic agents and have been demonstrated to induce differentiation in some myeloid leukemia cell lines. In this study, we show that HDAC inhibitors have a novel action on osteoclast differentiation. The effect of 2 HDAC inhibitors, trichostatin A (TSA) and sodium butyrate (NaB), on osteoclastogenesis was investigated using rat and mouse bone marrow cultures and a murine macrophage cell line RAW264. Both TSA and NaB inhibited t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
158
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 191 publications
(171 citation statements)
references
References 68 publications
(93 reference statements)
12
158
1
Order By: Relevance
“…Suppression of HDAC3 Inhibits Osteoclast DifferentiationPrevious reports indicated that the non-selective HDAC inhibitors TSA and NaB inhibit osteoclast formation (13). However, these data do not indicate the significance of individual HDACs to osteoclastogenesis.…”
Section: Resultsmentioning
confidence: 52%
See 2 more Smart Citations
“…Suppression of HDAC3 Inhibits Osteoclast DifferentiationPrevious reports indicated that the non-selective HDAC inhibitors TSA and NaB inhibit osteoclast formation (13). However, these data do not indicate the significance of individual HDACs to osteoclastogenesis.…”
Section: Resultsmentioning
confidence: 52%
“…Several studies have shown that HDIs, TSA, and NaB directly inhibit osteoclastogenesis (13,14). The current study is among the first to identify the HDACs to be involved in this inhibitory effect on osteoclast formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding may in part explain the clinically observed connection between CD38 expression in chronic lymphocytic leukemia and enhanced production of cytokines, such as IL-4 (17). Moreover, decreases in HDAC activity oppose osteoclast formation (27), thus providing another means through which CD38 hinders osteoclastogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…96 It is already known that HDAC inhibitors, such as trichostatin A, sodium butyrate and FR901228, can block osteoclastogenesis. 97,98 Recently, another HDAC inhibitor, PXD 101, was also shown to inhibit osteoclast formation synergistically with bortezomib. 99 Finally, other proteasome inhibitors, such as MG-132 and MG-262, reduce both osteoclast differentiation and activity of mature osteoclasts in vitro; 78,100 and others, such as epoxomicin, PS-1 and lactacystin, induce osteoblast function and bone formation.…”
Section: Effect Of Other Novel Anti-myeloma Agents On Bone Metabolismmentioning
confidence: 99%